Assessing Kidney Transplantation Using ECMO-Supported Donors Within a KDPI-Based Allocation System - Peter J. Altshuler, MD; Devon J. Pace, MD; William A. Preston, MD; Sage A. Vincent, MD; Ashesh P. Shah, MD; Jaime M. Glorioso, MD; Warren R. Maley, MD; Adam M. Frank, MD; Carlo B. Ramirez, MD; Sharon West, MS; Richard Hasz, Jr, MFS, CPTC; Adam S. Bodzin, MD (Transplantation Direct, 2023)
Background. Organ donors supported by extracorporeal membrane oxygenation (ECMO) have historically been considered high-risk and are judiciously utilized. This study examines transplant outcomes using renal allografts from donors supported on ECMO for nondonation purposes. Methods. Retrospective review of the Gift of Life (Pennsylvania, New Jersey, Delaware) organ procurement organization database, cross-referenced to the Organ Procurement and Transplantation Network database, assessed kidney transplants using donors supported on venoarterial (VA) and venovenous (VV) ECMO for nondonation purposes. Transplants using VA- and VV-ECMO donors were compared with Kidney Donor Profile Index (KDPI)-stratified non-ECMO donors. Regression modeling of the entire ECMO and non-ECMO populations assessed ECMO as predictive of graft survival. Additional regression of the ECMO population alone assessed for donor features associated with graft survival. Results. Seventy-eight ECMO donors yielded 128 kidney transplants (VA: 80, VV: 48). Comparing outcomes using these donors to kidney transplants using organs from KDPI-stratified non-ECMO donors, VA- and VV-ECMO donor grafts conferred similar rates of delayed graft function and posttransplant renal function to KDPI-matched non-ECMO counterparts. VA-ECMO kidneys demonstrated superior graft survival compared with the lowest-quality (KDPI 86%–100%) non-ECMO kidneys and similar graft survival to KDPI <85% non-ECMO kidneys. VV-ECMO showed inferior graft survival to all but the lowest-quality (KDPI 86%–100%) non-ECMO kidneys. VV-ECMO, but not VA-ECMO, was associated with increased risk of graft loss on multivariable regression (hazard ratios—VA: 1.02, VV: 2.18). Higher KDPI, advanced age, increased body mass index, hypertension, and diabetes were identified as high-risk features of ECMO donors. Conclusions. Kidney transplantation using appropriately selected ECMO donors can safely expand the donor pool. Ongoing studies are necessary to determine best practice patterns using kidneys from these donors.